The objective Effect of Internal and External Environment and its Psychological & Practical Reflection on the Political Decision-Making Process - م. د. أسراء شريف الكعود (College of Education for Women, 2019)
The objective Effect of Internal and External Environment and its Psychological & Practical Reflection on the Political Decision-Making Process